Virtual sign translator - Escudeiro, Paula (2013)
In this paper authors present the overall study that includes the model developed (VS Model) and the experiences performed, with an automatic bidirectional sign language translator, between written and sign language, which is being supervised by the research group GILT (Graphics, interaction & learning technologies) under the frame of a national project called Virtual Sign (VS project). This project aims to develop and evaluate a model that facilitates access for the deaf and hearing impaired to digital content - in particular the educational content and learning objects - creating the conditions for greater social inclusion of deaf and hearing impaired people. Access to digital content will be supported by an automatic translator between Portuguese Writing (LEP) and Portuguese Sign Language (LGP) supported by an interaction model.